2022
DOI: 10.1007/s13593-022-00772-w
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing co-design of agroecology-oriented cropping systems: lessons to build design-support tools

Abstract: If the challenges involved in agroecological transition are to be addressed, cropping systems (CS) need to be changed profoundly, which in turn requires innovative design adapted to local conditions. This is however by no means an easy task since such design activity requires extensive knowledge on objects and processes rarely studied until now, most of which is distributed amongst numerous stakeholders. Since the 2000s, research on design in agriculture has aimed at developing participatory methods to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Considerations of interactions between crop management and crop choices were thereby emphasized. This "functionbased reasoning" (Quinio et al 2022) was also visible in discussions about crop choices in order to reduce weed and pest issues. The need for break crops due to a limited number of registered herbicides and the inclusion of soybean as a break crop in maize monocultures were mentioned by Austrian and German actors, supporting findings from step 1.…”
Section: Lessons Learned For Redesigning Legume-supported Cropping Sy...mentioning
confidence: 98%
See 2 more Smart Citations
“…Considerations of interactions between crop management and crop choices were thereby emphasized. This "functionbased reasoning" (Quinio et al 2022) was also visible in discussions about crop choices in order to reduce weed and pest issues. The need for break crops due to a limited number of registered herbicides and the inclusion of soybean as a break crop in maize monocultures were mentioned by Austrian and German actors, supporting findings from step 1.…”
Section: Lessons Learned For Redesigning Legume-supported Cropping Sy...mentioning
confidence: 98%
“…While the Irish actors reported a reluctance of feed manufacturers to include more grain legumes such as faba bean, the network Schwäbisch Hall Producers reported on an expanded grain legume use as a valuable pig feed on farm resulting in premium prices for regional pork products. Previous workshops have also shown that mixing actors with different objectives can broaden the discussion (Quinio et al 2022).…”
Section: Lessons Learned For Redesigning Legume-supported Cropping Sy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, most cropping or farming systems are designed for one location, one farm and one environment, and differ from the ones designed elsewhere: farming system design is situated. To fuel such a situated design process, several authors stress the importance of mobilizing local knowledge of farmers, combined with scientific and technical knowledge (Leclère et al, 2018;Girard and Magda, 2020;Quinio et al, 2022), in a dynamics of open innovation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…En outre, plusieurs études soulignent que le processus de conception collective à l'oeuvre dans les transitions vers la durabilité est un processus de conception collaborative, c'est-à-dire un processus dialogique au sein duquel est mise en jeu une confrontation d'idées et de valeurs (par ex., Le Bail, Baker & Détienne, 2022 ;Quinio, Jeuffroy, Guichard, Salazar & Détienne, 2022). Ces travaux reposent sur une approche sociocognitive de la conception, c'est-à-dire qu'ils envisagent la conception comme un processus social de négociation entre différents points de vue, représentations ou disciplines (Bucciarelli, 1988 ;Détienne, Martin & Lavigne, 2005 ;Schön, 1988).…”
unclassified